2017
DOI: 10.24818/jamis.2017.04007
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory adoption of IFRS in emerging markets: the case of Turkey

Abstract: Abstract:European-listed companies and many emerging countries have been required to present their consolidated financial statements in compliance with the International Financial Reporting Standards (IFRS) since 2005. Having cross-border comparability and transparency with this uniform accounting system is expected to provide higher accounting quality and value relevance. Evaluation of financial performance in terms of value relevance of IFRS is not only vital for existing investors or stakeholders but also f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…After the switch to IFRS standards, the accounting numbers presented a weaker association with the stock price. The case of Turkey (Temiz and Güleç, 2017) showed on the contrary positive effect of IFRS adoption, it was confirmed that accounting information produced under IFRS became more value relevant. The study of IFRS adoption in Iraq (Khdir and Bialek-Jaworska, 2020) provided evidence that mandatory IFRS adoption didn't improve financial information comparability As far as it's known, there are no individual studies for Russia related to the comparability of financial information after IFRS adoption.…”
Section: Literature Reviewmentioning
confidence: 64%
“…After the switch to IFRS standards, the accounting numbers presented a weaker association with the stock price. The case of Turkey (Temiz and Güleç, 2017) showed on the contrary positive effect of IFRS adoption, it was confirmed that accounting information produced under IFRS became more value relevant. The study of IFRS adoption in Iraq (Khdir and Bialek-Jaworska, 2020) provided evidence that mandatory IFRS adoption didn't improve financial information comparability As far as it's known, there are no individual studies for Russia related to the comparability of financial information after IFRS adoption.…”
Section: Literature Reviewmentioning
confidence: 64%
“…Kargin (2013) found that the market value of Turkish firms was value relevant with respect to book value and earnings. Another research (Temiz & Gulec, 2017) in Turkey also highlights a gradual increase in the value relevance with the transition from local standards to IFRS. A comparative study in Jordan by Daas (2014) measured the impact on accounting quality during three phases i.e.…”
Section: H1: the Reported Earnings (Eps) And Equity Book Values (Bvps...mentioning
confidence: 97%
“…We followed the 'same firm-year' design during the entire period of study (Ibiamke & Ajekwe, 2017;Outa et al, 2017;Temiz & Gulec, 2017) and the complete sample of 5460 observations was used to test the value relevance as well as the impact of IFRS on value relevance. For the comparative analysis, the data were equally partitioned between the pre-mandatory convergence period (2013-14 to 2014-15) and post-mandatory convergence period (2017-18 to 2018-19).…”
Section: Population and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Turkish market, the transfer to IFRS triggered research on the influence of profit and net assets on stock prices from 2001 to 2008 [30]. The selection was divided into two sub-selections: before and after implementation of IFRS.…”
Section: Literature Reviewmentioning
confidence: 99%